1974
DOI: 10.1007/bf02532127
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peroxidized arachidonic acid upon human platelet aggregation

Abstract: Human platelet aggregation was studied in vitro following exposure to free arachidonic acid and peroxidized arachidonic acid. A slow aggregation response was caused by free arachidonic acid, whereas a rapid, marked response resulted from exposure to peroxidized free arachidonic acid. Aggregation resulting from peroxidized arachidonic acid was not counteracted by adenosine nor by prostaglandin E1, both in high concentrations. Peroxide‐induced platelet aggregation required the presence of added calcium ions in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…In concentrated solutions, however, heme proteins inhibit oxidation (46,47) (48) reported that oxidized rather than nonoxidized arachidonic acid caused a much more rapid and marked aggregation. Glass et al (49) …”
mentioning
confidence: 99%
“…In concentrated solutions, however, heme proteins inhibit oxidation (46,47) (48) reported that oxidized rather than nonoxidized arachidonic acid caused a much more rapid and marked aggregation. Glass et al (49) …”
mentioning
confidence: 99%
“…Mickel and Horbar (1974) reported that the platelet aggregation resulting from exposure to peroxidized arachidonic acid was abolished by prior treatment of the lipid peroxide with tocopherol and butylated hydroxytoluene . Previously we have demonstrated that vitamin E-nicotinate could inhibit lipid peroxide formation of platelets exposed to 11,0, (Higashi and Kikuchi 1974).…”
Section: Methodsmentioning
confidence: 99%
“…Accumulation of lipid peroxides in atheromatous plaques could predispose to thrombus formation by inhibiting generation of prostacyclin by the vessel wall without reducing TXA2 production by platelets. Moreover, platelet aggregation is induced by 15-HPAA and this aggregation is not inhibited by adenosine or PGE, (116). Human atheromatous plaques do not produce prostacyclin (1 17, 118).…”
Section: (D) Prostacyclin and Atherosclerosismentioning
confidence: 99%